Influence of onion skin powder on nutritional and quality attributes of wheat pasta. - Monika Michalak-Majewska; Dorota Teterycz; Siemowit Muszyński; Wojciech Radzki; Emilia Sykut-Domańska (PLoS ONE)
Onion skin is a waste produced during onion bulb processing. Recent studies have reported that it contains large amounts of bioaccessible and bioavailable compounds thus it can be used to design of novel food products. The objective of the study was an attempt to substitute semolina with onion skin (OS) powder in pasta at 2.5, 5 and 7.5 g/100 g levels. The effects on the chemical composition, antioxidant potential, technological and sensory properties of the fortified pasta samples were evaluated compared with a control sample. Fortification with OS resulted in a significant (P < 0.05) improvement in nutritional properties, which was demonstrated by an increase in the content of dietary fibre, ash, total phenolic compounds, flavonoids content and antioxidant activity (FRAP and DPPH). Cooking loss increased with increasing levels of OS, however, all pasta samples were in the acceptable range (8 g/100 g). Onion skin incorporation decreased optimal cooking time, water solubility index and increase redness (a*), compared to the control sample. Results of sensory evaluation suggest that pasta, in which 2.5% of the flour was replaced by this plant component, showed the highest value of the "overall quality". Our study indicates that onion skin powder can be a potential alternative for the food industry to provide nutritional enriched pasta.